2014
DOI: 10.1002/jmr.2385
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal transport of TRH analogs through PepT1: the role ofin silicoandin vitromodeling

Abstract: The present study involves molecular docking, molecular dynamics (MD) simulation studies, and Caco-2 cell monolayer permeability assay to investigate the effect of structural modifications on PepT1-mediated transport of thyrotropin releasing hormone (TRH) analogs. Molecular docking of four TRH analogs was performed using a homology model of human PepT1 followed by subsequent MD simulation studies. Caco-2 cell monolayer permeability studies of four TRH analogs were performed at apical to basolateral and basolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It has been reported that the residues Glu26, Trp294 and Tyr588 in PepT1 are associated with substrate recognition (affinity), suggesting that aromatic or basic amino acid residue may play a key role in PepT1 recognition (Meredith & Price, 2006). However, in silico analysis using tripeptidyl thyrotropin-releasing hormone analogues revealed the difficulty of quantitatively predicting peptide transport, since the affinity of PepT1 to peptides can be determined by their diverse chemical interactions (Bagul et al, 2014). For example, a lower PepT1 affinity for the D -amino acid-coupled peptidyl drug, acyclovir, compared to L -amino acid-coupled drug indicated that stereoisomerism must also be considered as a determining factor of PepT1 recognition (Talluri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the residues Glu26, Trp294 and Tyr588 in PepT1 are associated with substrate recognition (affinity), suggesting that aromatic or basic amino acid residue may play a key role in PepT1 recognition (Meredith & Price, 2006). However, in silico analysis using tripeptidyl thyrotropin-releasing hormone analogues revealed the difficulty of quantitatively predicting peptide transport, since the affinity of PepT1 to peptides can be determined by their diverse chemical interactions (Bagul et al, 2014). For example, a lower PepT1 affinity for the D -amino acid-coupled peptidyl drug, acyclovir, compared to L -amino acid-coupled drug indicated that stereoisomerism must also be considered as a determining factor of PepT1 recognition (Talluri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…3 Our studies regarding peptide-induced physiological functions also revealed that basic and/or hydrophobic small peptides, such as Trp-His, exerted vasorelaxation effects in the aorta through the retardation of intracellular Ca 2+ -signaling pathways, [4][5][6] and could be absorbed intact into the blood system via intestinal peptide transporter 1. [7][8][9] Peptides, which are condensed amino acids, have many members in their polymeric series, e.g., >400 di-peptides and >8000 tri-peptides, and simple and convenient assays for bioactive small peptides in food hydrolysates or natural materials are required in the food industry. It is difficult to separate small peptides in hydrolysates in a one run-in assay 10 in reversed-phase high-performance liquid chromatography (HPLC), because of their similar polarities and hydrophobicities.…”
Section: Introductionmentioning
confidence: 99%
“…TRH can be removed from the brain extracellular space by transport into brain cells; nevertheless, this event has a small V max and may have a very limited quantitative importance (Charli et al, 1984). The molecular entity that contributes to this transport has not been characterized; it may reflect TRH-R mediated endocytosis (Ashworth et al, 1995), or the action of a TRH transporter (Bagul et al, 2014).…”
Section: Introductionmentioning
confidence: 99%